Development of advanced combustion strategies for heavy duty LPG engines to achieve near-diesel efficiency - Fosudo, Toluwalase Jude, author; Olsen, Daniel B., advisor; Windom, Bret, committee member; Wise, Dan, committee member; Grigg, Neil, committee member (Colorado State University. Libraries, 2024)
As the transportation sector evolves in response to increasingly stringent emissions regulations and economic realities in the wake of the decarbonization drive, several no/low carbon fuel options have emerged as viable options for internal combustion engines. Among these fuels, Liquefied Petroleum Gas (LPG) is uniquely positioned for spark ignited engine operation due to its favorable physical and chemical properties. Currently, much of its use as an engine fuel is limited to light-duty applications, dual fuel applications, or retrofitted gasoline engines, with a lesser degree of penetration into the heavy-duty sector where diesel fuel still dominates. A key reason for this is the deficit in performance and efficiency between diesel and other low carbon fuels, including LPG, necessitating the need for targeted research aimed at bridging this gap, and positioning LPG as a fuel of choice in the heavy-duty sector. Two prominent drawbacks responsible for this gap between diesel and LPG engine performance are the dearth of specialized fuel injection hardware and tailored injection strategies, and knock, which limits the performance of spark ignited engines. This work seeks to address these and other limitations and achieve near diesel efficiency on a heavy-duty engine platform. Two engine platforms were employed in this study. A cooperative fuel research (CFR) spark-ignited engine was used to study the knock dynamics and the performance, combustion, and emissions behavior of the LPG fuel in relation to key engine parameters, the LPG fuel composition, and other low carbon fuel options. Compression ratio, engine load, exhaust gas recirculation percents, and a novel combustion control tool, the combustion intensity metric (CIM), were all varied on the CFR engine and a computational fluid dynamics (CFD) model calibrated and validated. Key findings were then transferred to a heavy-duty engine platform, the Cummins ISX15L single cylinder engine. The engine is a converted 6-cylinder diesel engine with diesel brake thermal efficiency (BTE) of 44%. A baseline evaluation was conducted with liquid LPG port-injected at 16bar and 9.3:1 compression ratio. Then the engine was switched to direct injection (DI) configuration with a fuel delivery system capable of delivering liquid LPG at pressures up to 200bar. Three principal configurations were developed for operation of the heavy-duty engine employing a gasoline direct injector (GDI) with nozzle patterns adapted for optimal distribution of the LPG fuel in the combustion chamber, a GDI modified for higher LPG flow and a double-injector port-fuel injection (PFI) system optimized for injection location, and charge cooling and distribution. The experiments and modeling contained in this study demonstrate the impact of LPG composition on engine performance, the mitigating effect of EGR on knock and NOx emissions, the potential for a better controlled combustion using the CIM tool and the advantages in terms of knock, performance, and emissions of designing an injection strategy tailored to the LPG fuel. The results show that the heavy-duty engine operated on LPG achieved the target efficiency of 44% BTE at high EGR, high compression ratio, and high load conditions for both DI and PFI configurations. The outcomes of this study advance the literature on knock, end-gas autoignition, emissions, and EGR related to LPG and its use as a choice fuel for heavy-duty applications and advances the development of specialized fuel delivery hardware and injection strategies for the LPG fuel.
Keywords: direct and port fuel injection; exhaust gas recirculation; internal combustion engines; emissions; alternative fuels; heavy-duty engine efficiency